Privacy, surveillance, and implanting RFID microchips to humans* - Bardakçı, Tayyibe (International Journal of Human and Health Sciences (IJHHS), 2024)
Background: Radio Frequency Identification (RFID) technology is specifically designed for the remote identification of objects. The first patent for human implantable RFID microchips was granted in 1997, and the FDA approved these microchips in 2004. Since then, they have found applications in humans for diverse reasons. Objective: This study aims to make an ethical evaluation of using RFID microchips in humans, focusing on privacy and surveillance. Methods: A literature review was conducted, exploring the conceptual dimensions of privacy and surveillance, and ethical evaluations were made regarding potential privacy violations caused by RFID microchips, as well as their potential uses for surveillance purposes. Results: Privacy is a multidimensional concept that spans various disciplines such as psychology, sociology, anthropology, medicine, theology, and law, and throughout history it constitutes an indispensable and intrinsic necessity for humanity. On the other hand, surveillance is a process wherein certain groups employ methods to gather, accumulate, analyze, process, and utilize data, with the objective of regulating the behavior of specific groups, entailing potential physical, ideological, or structural interventions, ultimately aiming to guide individuals toward predetermined behavioral patterns. Discussion and Conclusion: A major concern with RFID microchips is potential privacy violations and their use for surveillance. These microchips and their connected networks hold a significant amount of information, including sensitive data like healthrelated information. Thus, they make individuals become easily identifiable and make them vulnerable to surveillance practices. International Journal of Human and Health Sciences Vol. 08 No. 01 Jan’24 Page: 84-94